Optimal Forecasting of Resources and Production Capacity of the Libyan Iron and Steel Company to Cover Demand for Its Products - Omar Azouza; Madi Naser; Elganidi Hassan (Techno LPPM, 2021)
The Libyan Iron and Steel Company (LISCo) is considered one of the largest industrial companies with capacity is about 1,324,000 tons of liquid steel annually by direct reduction of iron pellets using local natural gas. One of the most difficult problems facing the management is the optimal use of its resources and production capacity needed to cover the volume of demand for its products. In order to meet the needs of its customers in a timely manner and at the lowest possible cost, which requires the use of quantitative techniques as a tool to support and rationalize the economic decision. These problems cannot be solved out of personal judgment. Rather, this requires the use of modern quantitative methods that contribute to making the optimal decision. Among the most important of these are prediction techniques. The importance of the study is represented in forecasting the production capacity and that leads to the optimum utilization of LISC’s resources. The study was carried out first by relying on data and information gathering to review previous studies, research and scientific journals. Secondly, through field visits. Third, apply the equations and laws of demand forecasting of simple linear regression to the data obtained. Fourth, using Microsoft Excel on the data collected. We obtained good results with which we can support the senior management of LISC, with 95% & 99% confidence. We recommended LISC does not control costs, and price and securing a fixed profit margin, in addition to the company bearing additional costs resulting from the creation of interests.